A note on the incidence of reproductive disorders in buffaloes in Guntur district of Andhra Pradesh - NAIDU, G V; RAO, K BABU (The Indian Journal of Animal Reproduction, 2023)
Incidence of various reproductive disorders in buffaloes of Guntur District of AP revealed true anestrum and repeat breeding were found to be the major gynaecological problems, followed by endometritis.